In vivo evaluation of the lysine‐specific demethylase (KDM1A/LSD1) inhibitor SP‐2577 (Seclidemstat) against pediatric sarcoma preclinical models: A report from the Pediatric Preclinical Testing Consortium (PPTC). Issue 11 (28th August 2021) - Kurmasheva, Raushan T.; Erickson, Stephen W.; Han, Ruolan; Teicher, Beverly A.; Smith, Malcolm A.; Roth, Michael; Gorlick, Richard; Houghton, Peter J.
Abstract: SP‐2577(Seclidemstat), an inhibitor of lysine‐specific demthylase KDM1A (LSD1) that is overexpressed in pediatric sarcomas, was evaluated against pediatric sarcoma xenografts. SP‐2577 (100 mg/kg/day × 28 days) statistically significantly ( p < .05) inhibited growth of three of eight Ewing sarcoma (EwS), four of five rhabdomyosarcoma (RMS), and four of six osteosarcoma (OS) xenografts. The increase in EFS T/C was modest (<1.5) for all models except RMS Rh10 (EFS T/C = 2.8). There were no tumor regressions or consistent changes in dimethyl histone H3(K4), HOXM1, DAX1, c‐MYC and N‐MYC, or tumor histology/differentiation. SP‐2577 has limited activity against these pediatric sarcoma models at the dose and schedule evaluated.